Compatibilization and ultraviolet blocking of PLA/PCL blends via interfacial localization of titanium dioxide nanoparticles. Issue 6 (30th September 2017) - Decol, Marindia; Pachekoski, Wagner M.; Becker, Daniela
ABSTRACT: In this work, the effect of TiO2 addition over morphological and ultraviolet (UV) blocking properties of poly(lactic acid) (PLA) and poly(ɛ‐caprolactone) (PCL) blends was investigated. The micrographs showed a partially co‐continuous structure in the PLA/PCL blend with 42/58 (wt %/wt %) and the TiO2 nanoparticles addition leads to a structural phase inversion, i.e., continuous PCL and partially continuous PLA with a dispersed portion. TiO2 nanoparticles were observed to be preferably localized at the interface of the two phases due to kinetic effects (large difference between the melting temperatures) and nanoparticle geometry (low aspect ratios). An adhesion improvement between the phases and morphological stability were observed with the addition of TiO2 nanoparticles. This behavior indicates that the nanoparticles can act as compatibilizers due to their localization at the interface between the two phases. The UV light absorption and transmission percolation threshold occurred with 1.5% TiO2 in the 42PLA/52PCL blend. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45813. Abstract :